An Adaptive Event-Triggered Synchronization Approach for Chaotic Lur’e Systems Subject to Aperiodic Sampled Data - Wang, Yueying; Karimi, Hamid Reza; Huaicheng Yan (IEEE transactions on circuits and systems. II, Express briefs, 2019)
This brief deals with the problem of master–slave synchronization for chaotic Lur’e systems with aperiodic sampled data. Specifically, a novel aperiodic adaptive event-triggered communication mechanism is introduced to reduce the transmission load, which covers the previous ones as special cases. By partially resorting to the time-dependent Lyapunov function, a new synchronization criterion is derived, which depends on both the upper and lower bounds of variable sampling interval. Finally, Chu’s circuit system is chosen as an illustrative example to show the virtue and effectiveness of the achieved synchronization strategies.